Cytotoxic Oleanane-type Saponins from Albizia inundata - Zhang, Huaping (2011)
Bioassay-guided fractionation of a CH(2)Cl(2)-MeOH extract of the aerial parts of Albizia inundata resulted in the isolation of two new natural oleanane-type triterpene saponins {3-O-[α-L-arabinopyranosyl( 1→6)]-2-acetamido-2-deoxy-β-D-glucopyranosyl oleanolic acid (1) and 3-O-[α-L-arabinopyranosyl(1→2)-α-L-arabinopyranosyl(1→6)]-2-acetamido-2-deoxy-β-D-glucopyranosyl acacic acid lactone (2)} along with seven known saponins {3-O-[α-L-arabinopyranosyl(1→6)]-2-acetamido-2-deoxy-β-D-glucopyranosyl echinocystic acid (3), 3-O-[β-D-xylopyranosyl (1→2)-α-L-arabinopyranosyl (1→6)]-2-acetamido-2-deoxy-β-Dglucopyranosyl acacic acid lactone (concinnoside D) (4), 3-O-[β-D-glucopyranosyl (1→2)]-β-D-glucopyranosyl oleanolic acid (5), 3-O-[α-L-arabinopyranosyl (1→2)-α-L-arabinopyranosyl (1→6)]-β-D-glucopyranosyl oleanolic acid (6), 3-O-[β-D-xylopyranosyl (1→2)-α-L-arabinopyranosyl (1→6)]-β- D-glucopyranosyl oleanolic acid (7), 3-O-[α-L-arabinopyranosyl- (1→2)-α-L-arabinopyranosyl-(1→6)-[β-D-glucopyranosyl-(1→2)]-β-D-glucopyranoside echinocystic acid (8) and 3-O-[β-D-xylopyranosyl-(1→2)-α-L-arabinopyranosyl-(1→6)-[β-D-glucopyranosyl-(1→2)]-β-D-glucopyranoside echinocystic acid (9)}. The structures of 1 and 2 were established on the basis of extensive 2D NMR ((1)H-(1)H COSY or DQF-COSY, HSQC, HMBC, TOCSY, and HSQC-TOCSY) spectroscopic, ESIMS, and chemical methods. Saponins 1, 3, 6, and 7 showed cytotoxicity against human head and neck squamous cells (JMAR, MDA1986) and melanoma cells (B16F10, SKMEL28) with IC(50) values in the range of 1.8–12.4 μM, using the MTS assay.